Pengaruh Live Streaming, Flash Sale, Dan Big Sale Shopee Terhadap Perilaku Konsumtif Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Jambi Dalam Prespektif Ekonomi Islam - Sari Halizah Panggabean; Rafiqi Rafiqi; Muhammad Roihan (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to determine the effect of live streaming, flash sales and big sales shopee on consumptive behavior among students. This research was conducted at the Faculty of Economics and Business, University of Jambi. The method used in this research is a quantitative method. The technique used in sampling is purposive sampling technique. The number of samples taken was 98 respondents from a population of 4,300. Data collection in this study was carried out using a questionnaire. The data analysis technique in this study was carried out using the SmartPLS 4 application program. The results showed that partially live streaming (X1) did not have a significant effect on consumptive behavior, flash sales (X2) had a significant effect on consumptive behavior and big sales (X3) did not have a significant effect on consumptive behavior. Simultaneously live streaming, flash sales and big sales shopee have an effect on consumptive behavior